Atendimento inicial ao queimado em unidades de urgência : conhecimento teórico de estudantes de enfermagem - Meschial, William Campo (2013)
It is believed that the academic training of a critical and reflective nurse, able to take scientifically based decisions in situations of urgency and emergency, as in the initial care of burns victims , should be structured in undergraduate courses . Thereby, the present study aimed to analyze the theoretical knowledge of undergraduate nursing students on the initial assistance to burned victims (IABV) in urgency units. A descriptive, exploratory study of mixed approach was conducted. The qualitative approach involved curriculum analysis and interviews with four Undergraduate Nursing courses coordinators of the metropolitan area of Maringá; the quantitative consisted of applying a modular questionnaire , structured and self-administered, to one hundred and seven students enrolled in the last semester of nursing degree courses from the same institutions, with questions on socio - demographic and economic profile; sources of information and school situation; personal interest and prior contact with thematic study , and knowledge about the IABV in urgency units. Qualitative data were subjected to thematic content analysis, and quantitative data to descriptive and association chi-square test, using the software Epi Info 7®. The course coordinators were, in its entirety, nurses, being one Ph.D. and three with master´s degree. Training time on nursing ranged from 17 to 30 years, and the time in the role of coordinator of the nursing program at the surveyed institution ranged from one to 12 years. As for nursing students , 90.7 % were women , aged 20-24 years (63.6 % ) , self - declared white ( 63.6 % ) and single ( 82.2 % ) . Out of this population, 94.4 % lived in urban area, 63.8 % had a family income situated between three and seven times the minimum wage and 46.2 % were currently employed , with workloads between four and six hours a day , along with the academic journey . It was found that the IABV is implicit in the curriculum of two, out of four analyzed courses, however incomplete, but from interviews with program coordinators was identified a "hidden curriculum" developed in these courses, yet, still deficient. Was also highlighted the need for the IABV be structured in undergraduate courses, the importance of theoretical-practical approach and the call to curriculum adaptation to teaching qualification in this area . Regarding the treatment experience of the students to burn victim, over 94 % reported that the IABV was approached in theory subjects in graduation, but 81.6 % considered that approach insufficient. About the relationship between theory and practice approach, 47.7 % participated in extracurricular theoretical activities, but only 28.0 % had practical activities of the IABV. All the students felt it was important to approach this subject in graduation and 38.7 % considered it extremely important for professional practice, but 41.1 % had little or no affinity with this theme. To what concerns knowledge, it was found that only 22.4 % of students showed it as satisfactory (≥60 %) and there was association between belonging to a public education institution and have performed nursing care in the initial care to burn victims, and have experienced the IABV with higher chances of satisfactory knowledge. We conclude that was found to be inadequate the approach to IABV training of nurses in the area under study, evidenced by gaps in training, pointed by nursing students and by their unawareness about the IABV. These data reveal the need to (re)consider teaching strategies that promote improvements related to academic nursing.